Effects of additives and post‐treatment on the thermoelectric performance of vapor‐phase polymerized PEDOT films. Issue 23 (18th August 2017) - Jia, Yanhua; Li, Xuejing; Jiang, Fengxing; Li, Changcun; Wang, Tongzhou; Jiang, Qinglin; Hou, Jian; Xu, Jingkun
ABSTRACT: Vapor‐phase polymerization (VPP) is an important method for the fabrication of high‐quality conducting polymers, especially poly(3, 4‐ethylenedioxythiophene) (PEDOT). In this work, the effects of additives and post‐treatment solvents on the thermoelectric (TE) performance of VPP‐PEDOT films were systematically investigated. The use of 1‐butyl‐3‐menthylinidazolium tetrafluoroborate ([BMIm][BF4 ], an ionic liquid) was shown to significantly enhance the electrical conductivity of VPP‐PEDOT films compared with other additives. The VPP‐PEDOT film post‐treated with mixed ethylene glycol (EG)/[BMIm][BF4 ] solvent displayed the high power factor of 45.3 μW m −1  K −2 which is 122% higher than that prepared without any additive or post‐treatment solvent, along with enhanced electrical conductivity and Seebeck coefficient. This work highlighted the superior effect of the [BMIm][BF4 ] additive and the EG/[BMIm][BF4 ] solvent post‐treatment on the TE performance of the VPP‐PEDOT film. These results should help with developing the VPP method to fabricate high‐performance PEDOT films. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1738–1744 Abstract : 1‐Butyl‐3‐menthylinidazolium tetrafluoroborate ([BMIm][BF4 ]) is a typical ionic liquid. The introduction of [BMIm][BF4 ] in the VPP process of EDOT has a significant impact on the thermoelectric performance of PEDOT films.